Teacher Behavior that Fosters Positive Relationships Between Teachers and Students - Ode Yahyu Herliany Yusuf; Devi Andrianti; Lilis Endriani; Irlika Taunar; Salmia Salmia; Rusiana Rusiana; Rustia Rustia (CV. Rayyan Dwi Bharata, 2023)
Being a teacher is not an easy job, one of the things that a teacher needs to do is to be able to build a positive relationship between teacher and student, this is the purpose of this research which is to find out how to better build good relationships and make a good response in order to produce a positive relationship between teacher and student. Data from this study was sourced from books and electronic scientific articles. With data collection techniques using content analysis research techniques with the aim of helping teachers in building good relationships or positive relationships and building a good image of teachers in the student environment. In addition, it is one of the considerations in the benchmark of how to behave and how to respond to students so that positive relationships can be built between teachers and students.